DINÂMICA DE SISTEMAS PARA ANALISAR O IMPACTO ECONÔMICO DE UMA AGÊNCIA DE INOVAÇÃO EM UMA INSTITUIÇÃO PÚBLICA Systems dynamics to analyze the economic impact of an innovation agency in a public institution - Rodrigues, Glauco Oliveira; Drago, Henrique Faverzani; da Silva, Gustavo Chiapinotto; Simonetto, Eugênio de Oliveira; Santos, Wellington Furtado; Bulé, Anieli Ebling (Informe GEPEC, 2021)
This research presents a financial economic analysis of the Agency of Innovation and Technology Transfer (AGITTEC) of the Federal University of Santa Maria (UFSM). With the intention of contributing to the scientific knowledge of the area, this article was built with a research problem defined in verifying how much AGITTEC needs to generate revenue so that it can be self-financed. A research protocol was systematized according to the dynamic systems method consistent with the required methodological rigor. The contribution of this research is linked to a discussion of the favorable results and benefits of the relationship between university and agency, which can extend to improve the competitiveness of companies by presenting a better development. The study served to verify that despite the revenues, There is a heavy dependence of the agency on UFSM resources, and about 90% of its costs and expenses.